Pelatihan Digital Branding Kampung Wisata Bagi Kompepar Kampung Pulo Geulis Bogor - Farida Hariyati; Yulia Rahmawati; Deni Adha Akbari (Jurnal Media Pengabdian Komunikasi, 2023)
The Tourism Driving Group (Kompepar) is one of the community groups committed to support the government in developing tourism based on local wisdom. Kompepar Pulo Geulis consists of residents of the Pulo Geulis community who have concern and responsibility and play a role as a driving force in supporting the creation for the growth and development of tourism, as well as its benefits for people's welfare. Pulo Geulis is one of the ethnic tourism village that promotes tolerance for diversity. Despite their different beliefs, the people of Pulo Geulis live in harmony and respect one another. The people concern for diversity by maintaining tolerance between religious communities. This can be seen in the historical heritage that is still standing strong and as a witness of the religious harmony of the people around Pulo Geulis, namely the Maha Brahma Temple or Pan Kho Temple. Nevertheless, the branding of Pulo Geulis as an ethnic and tolerance tourism destination, has not been supported by the ability of its members of Kompepar Pulo Geulis, to communicate digitally to introduce their region. Therefore, the UHAMKA community service team held a training of digital branding for tourism village. This program aimed to strengthen digital branding understanding and practices among Kompepar members through digital communication media and plan several strategies for increasing the branding of Pulo Geulis. The methods used in this community service were observation, discussion, training, implementation and evaluation. The results showed some implementation of digital branding through digital media, namely website, Instagram, and YouTube.